Natural history of idiopathic abducens nerve paresis in a young adult - Jameel Rizwana Hussaindeen; Revathy Mani; Archayeeta Rakshit; Srikanth Ramasubramanian; Smitha Vittal Praveen (Journal of Optometry, 2016)
The natural history of idiopathic abducens nerve paresis and the role of conservative management such as vision training during the recovery process is not well documented in the literature to the best of our knowledge. This case report presents the natural recovery process of idiopathic abducens nerve paresis in a young adult and the role of vision therapy in the recovery process.